Effectiveness and Safety of Opioid-Free Anaesthesia and Analgesia in pain control and postoperative recovery of patients undergoing gynaecologic oncologic surgery: a retrospective cohort study - Jose Alexander Puentes Garcia; Daniel Rivera Tocancipa; Eugenio Medina; Julián Jovel Díaz; Pisso; Vincent Jean Carlo García Gil; Fredy Leonardo Carreño Hernandez (BMC Anesthesiology)
Abstract Background Opioids have been essential for the anesthesiologic management of patients undergoing surgical procedures such as gynecologic oncology, but incorrect dosage can lead to unwanted hemodynamic effects. Opioid-free anesthesia (OFA) and multimodal postoperative analgesia techniques can solve this problem as they can restrict the excessive use of opioids. Methodology A retrospective observational cohort study was conducted by reviewing the medical records of patients at the Hernando Moncaleano Perdomo University Hospital. Female patients who underwent gynecologic oncology surgery at the MPUHN and who received OFA, or opioid-based anesthesia (OBA) were identified. Two cohorts were created in which one have all patients (unadjusted cohort) and one with randomly selected patients (adjust cohort). Data on pain were collected using a visual analog pain scale (VAPS), along with hemodynamic variables and adverse events at 7 different times from admission to the operating room until discharge from the hospital. A bivariate analysis was performed between OFA and OBA, comparing frequencies of VAPS and adverse events with chi2, while mean difference for hemodynamic variables with t student. A multivariate analysis was performed with multiple logistic regression to evaluate differences in frequency of VAPS between OFA and OBA. Results For unadjusted cohort, difference was identified for greater pain in OFA than in OBA (p < 0.001) for the times before surgery, recovery room, and 24 h after surgery, while differences were only identified at recovery room in the adjusted cohort. The heart rate has significant differences only at pre-surgery, 30 min of induction and admission to the recovery room. Respiratory rate has significant differences at admission to the operating room, 30 min of induction. Mean arterial pressure was significant only in the recovery room and for oxygen saturation at admission to the operating room and discharge from recovery. Higher frequency of requiring antiemetics was only identified in patients with OFA than OBA on the fifth day of surgery. Significance was identified in multivariate analysis between OBA and OFA for at discharge from recovery room. Conclusions The OFA technique for gynecologic oncologic surgery patients has a similar impact on pain control compared to OBA. Trial registration Does not apply.